Hexagon Model for Local Economic Development: Unlocking Green Job Opportunities in Bali’s UMKM Sector as a Model for the Global South - Priadarsini S, Ni Wayan Rainy; Wiranata, I Made Anom; Listya Dewi, Ni Nyoman Clara; Parameswari, Anak Agung Ayu Intan (AEGIS : Journal of International Relations, 2025)
Bali’s Micro, Small, and Medium Enterprises (MSMEs) are increasingly adopting green business models to sustain local enterprises in line with the Sustainable Development Goals (SDGs). With their significant role in the regional economy, Bali’s MSMEs have the potential to advance sustainable practices while creating inclusive green jobs. This study analyzes the application of the Hexagon Model for Local Economic Development (LED), combined with the big push theory, to unlock these opportunities. Using qualitative methods through interviews and literature review, the findings highlight the need to strengthen ecosystems and resources to enable MSMEs to generate effective, productive, and inclusive jobs. Despite strategic potential, green MSMEs face challenges such as low awareness of eco-friendly practices, limited financing, and weak cross-sector collaboration. The Hexagon Model offers a structured framework for policymakers and practitioners to build synergy, broaden perspectives, and formulate concrete strategies for sustainable job creation. By linking upstream and downstream actors in local business ecosystems, Bali’s green MSME sector emerges as a replicable model for the Global South, generating opportunities for both the productive-age population and marginalized groups, including persons with disabilities.Keywords: